#### Answer

{11}

#### Work Step by Step

6x - 3 = 63
Step 1: Add 3 on both the sides
6x -3 + 3 = 63+3
Step 2: Simplify
6x = 66
Step 3: Divide both the sides by 6
$\frac{6x}{6}$ = $\frac{66}{6}$
Step 4: Simplify
x = 11
Now we check the proposed solution, 11, by replacing x with 11 in the original equation.
Step 1: the original equation 6x - 3 = 63
Step2: Substitute 11 for x
6.11 - 3 = 63
Step 3: Multiply 6.11= 66
66 -3 =63
Step 4: Subtract 66-3 = 63
63 = 63
Since the check results in true statement, we conclude that the solution set of the given equation is {11}